KONSEP METODE TILAWATI DALAM MEMUDAHKAN PEMBELAJARAN AL-QUR’AN PADA SISWA KELAS V - Lina Mariana; Nurhasan; Nurjanah (STIT Sirojul Falah Bogor, 2026)
Qur'anic learning at the elementary school level plays an important role in developing students' Qur'anic literacy and fostering their religious character. However, challenges such as limited reading fluency, inaccuracies in applying tajwid rules, and differences in students' learning abilities are still commonly encountered. This study aims to analyze the concept and implementation of the Tilawati method in facilitating Qur'anic learning among fifth-grade students at SD Islam Anugerah Insani Cibinong Bogor. The study employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, and analyzed using data reduction, data display, and conclusion-drawing techniques. The findings indicate that the Tilawati method is implemented through the principles of talaqqi and musyafahah, the use of the rost melody, and a combination of classical and individual learning approaches. The method was found to improve students’ reading fluency, accuracy in pronouncing Arabic letters (makharij al-huruf), and ability to apply tajwid rules correctly. In addition, it enhanced students’ learning motivation, self-confidence, and active participation during learning activities. The successful implementation of the method was supported by teacher competence, school support, and parental involvement, while limited instructional time and differences in students’ abilities remained challenges. Therefore, the Tilawati method is an effective and relevant strategy for improving Qur'anic literacy among elementary school students.